PENERAPAN ASUHAN KEPERAWATAN PADA PASIEN HIPERTENSI DI RUANG PENYAKIT DALAM I RSUD ENDE: - Sekunda, Maria S.; Cahyani, Sisilia Leny; Bai, Marieta K. S.; Doondori, Anatolia K. (Poltekkes Kemenkes Kupang, 2024)
Hypertension becomes a serious problem of public health, because if not controlled will develop and cause harmful complications. The consequences can be fatal due to frequent complications, such as stroke (brain hemorrhage), coronary heart disease, and renal failure (Gunawan, 2001). The purpose of the case study to describe nursing care in patient with hypertension in the room of the disease in III is carried out in a comprehensive process with nursing. The method used in case studies in patient with hypertension is a case study with a nursing process approach implemented on 3-5 may 2023 at the internal Medicine room I of Ende hospital. The results of the case study showed that the client complained of dizziness, headache, blurred eyes, neck tension, weakness, nausea, grimacing face, pain scale 5, looked weak, attached NaCl infusion 20 tts/min on the right hand, blood pressure 170/100 mmHg, pulse 104 x/min, temperature 375 0C, breathing 22 x/min, CRT < 3 seconds. The nursing diagnosis appointed is resti decreased cardiac output and pain discomfort disorders. All interventions are structured based on the appointed nursing diagnosis. After 3 days of implementation, the results obtained were that the problem of resting decreased cardiac output did not occur and the pain discomfort was resolved in part thanks to the cooperation of patients, families and caregivers.